The Effects of Leader Emotional Intelligence, Leadership Styles, Organizational Commitment, and Trust on Job Performance in the Real Estate Brokerage Industry - Lee, Chun-chang; Li, Yei-shian; Yeh, Wen-chih; Yu, Zheng (Frontiers in Psychology, 2022)
This study examines the effects of leader emotional intelligence, leadership styles (transformational and transactional), organizational commitment, and trust on job performance. A questionnaire was administered to the participants, who were real estate brokers in Kaohsiung City. Of the 980 questionnaires administered, 348 valid responses were received, indicating an effective response rate of 35.5%. Structural equation modeling was used for the analysis. The results show that leader emotional intelligence has a significant and positive effect on trust in supervisors, and transformational leadership and trust within a team have significant and positive effects on job performance. In addition, organizational commitment has a significant and positive effect on job performance. Trust within a team mediates the significant and positive effect of leader emotional intelligence on job performance. Although transactional leadership has no direct, positive, and significant effects on employee job performance, trust in the workplace shaped by a leader’s leadership style will empower a team’s spirit and boost their morale, thereby indirectly affecting their job performance in a positive manner.